STREAM: A structural macro-econometric model of the Maltese economy - Owen Grech; Noel Rapa (Central Bank of Malta, 2016)
This paper presents the third version of the Central Bank of Malta's core macro-econometric model of the Maltese Economy, STREAM (Structural and TRaditional Econometric model for Malta). It is a traditional structural model built around the neo-classical synthesis. Behavioural equations are estimated in error-correction form on the basis of quarterly data spanning from 2000Q1 to 2013Q4. Economic agents are assumed to have adaptive expectations. The novelty of the model is that it contains fully fledged fiscal and financial blocks, which is uncommon in traditional structural models.
Keywords: C3; C5; E1; E2; 330